(untitled) (JEMARI (Jurnal Edukasi Madrasah Ibtidaiyah), 2025)
Abstract The Merdeka Curriculum represents an evolution of the 2013 Curriculum, focusing on designing learning activities as a process for acquiring knowledge and experience through active student involvement. This approach requires teachers to adjust their teaching strategies to align with the principles of the Merdeka Curriculum, where the teacher’s role shifts to that of a facilitator, and students are encouraged to take an active role in their learning journey. This study explores the implementation of the Merdeka Curriculum using the Project-Based Learning (PJBL) model in mathematics instruction at SDTQ Al Ihsan Blimbing. The research adopts a qualitative descriptive method with a case study approach, gathering data through interviews and observations. Participants include the school principal and the grade 4 teacher at SDTQ Al Ihsan Blimbing. Data analysis is conducted through the processes of data reduction, data presentation, and drawing conclusions. The findings indicate that the Merdeka Curriculum with the PJBL model has been applied only in grades one and four. The implementation of PJBL in mathematics teaching involves stages such as planning and execution, which promote active student participation and create learning experiences that are effective, engaging, and enjoyable. Keywords: Independent Curriculum, Project Based Learning, Mathematics Abstrak Kurikulum merdeka merupakan pengembangan dari kurikulum 2013 yang berfokus pada perencanaan kegiatan belajar bagi siswa untuk memperoleh pengetahuan dan pengalaman melalui kegiatan di mana mereka berpartisipasi secara aktif. Diharapkan perubahan kurikulum ini akan memungkinkan guru untuk menyesuaikan model pembelajarannya dengan prinsip kurikulum independen. Guru berperan sebagai pembimbing atau mediator dan siswa menjadi peserta aktif dalam proses pembelajaran. Tujuan penelitian ini adalah menganalisis implementasi kurikulum merdeka dengan model Project Based Learning (PJBL) pada kelas matematika di SDTQ Al Ihsan Blimbing. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskriptif dengan menggunakan metodologi studi kasus. Data penelitian dikumpulkan melalui wawancara dan observasi terhadap partisipan penelitian, kepala sekolah dan guru kelas IV SDTQ Al Ihsan Blimbing. Proses analisis data dilakukan dengan tahapan meliputi pengurangan data, pengorganisasian data untuk disajikan, dan penarikan kesimpulan.. Penelitian ini menemukan bahwa pendekatan kurikulum merdeka melalui model PJBL hanya diterapkan di kelas satu dan empat. Penerapan PJBL dalam pembelajaran matematika melibatkan tahap perencanaan dan pelaksanaan dengan partisipasi aktif siswa, sehingga proses pembelajaran menjadi lebih efektif, menyenangkan dan menarik. Kata Kunci: Kurikulum Merdeka, Proyek Pembelajaran, Matematika